From Consultation to Participation: The Impact of Beneficiaries on Nonprofit Organizations' Decision Making and Output. Issue 3 (30th October 2015) - Wellens, Lore; Jegers, Marc
Abstract : Empirical research in the literature on accountability of nonprofit organizations (NPOs) toward their beneficiaries is scarce, and the available studies have a number of limitations. Our study attempts to overcome some of them and focuses on one specific component of accountability toward beneficiaries: beneficiary impact on organizational decision making and output. Data were collected by surveying general managers of 790 Belgian NPOs in fourteen industries. Results show that most NPOs implement some mechanisms to involve beneficiaries and their representatives in organizational policy making, mechanisms that vary between and within industries. Despite the existence of such mechanisms, their perceived association with impact on policy making and associated potential organizational effects is weak, though positive.